Stitching phospholanes together piece by piece: new modular di- and tridentate stereodirecting ligands - Lloret Fillol, Julio; Kruckenberg, Achim; Scherl, Peter; Wadepohl, Hubert; Gade, Lutz H. (Chemistry - a European journal, 2011)
The modular one-pot synthesis of a large family of bi- and tridentate 2,5-dimethyl- and 2,5-diphenyl-substituted phospholanes employs air-stable chiral phospholanium chloride salts and primary amines or NH4Cl as starting materials. These were transformed into the C2-symmetric dimethyl- and diphenylphospholane ligands, which reacted with [Rh(cod)2]BF4 (cod=1,5-cyclooctadiene) to yield the rhodium complexes [Rh(L)(cod)]BF4 (L=bisphospholane ligands). The corresponding trisphospholane complexes, 11 and 12, were obtained in high yields (81 and 92 %, respectively), and fully characterised by NMR spectroscopy, mass spectrometry and elemental analysis. Whilst in the C3-symmetric complex 11, containing the tridentate 2,5-dimethylphospholane, the ligand is bound symmetrically, different coordination behaviour was found for the diphenyl-substituted complex 12, in which the coordination of only two of the three phospholane moieties to the metal centre was observed. A DFT study at the B3PW91 level established minimum energy structures consistent with experimental findings in solution and in the solid state. The non-coordinated phospholane unit present in 12 allowed further modification of the complex through the coordination of AuIX (X=Cl, C6F5 and tris(trifluoromethyl)phenyl (FMes)) fragments to the pendant phosphane. To investigate the potential of the new ligands, the enantioselective hydrogenation of a series of prochiral olefins as benchmark substrates, using isolated Rh complexes as catalysts, was studied. The substrates included methyl esters of three dehydro-α-acetamido acids and two itaconic acid derivatives. In general good to excellent enantioselectivities (of up to >99 % ee) were observed. Ligand backbone modification by coordination of bulky AuX substituents to the free phospholane unit in complex 12 led to an outstanding enhancement of the catalyst performance and there was a clear correlation between the properties of the complex periphery and the enantioselectivity.